Fuzzy logic controller for a partially simulated chemical reactor system - Wahab, Ahmad Khairi Abdul; Hussain, Mohd Azlan; Omar, Rosli (2009)
ABSTRACT :In this work, a PARtially Simulated EXothermic chemical reactor (PARS-EX) pilot plant available in our department is utilized to implement and test various conventional and advanced control strategies. In this reactor, an exothermic reaction is simulated, where heat energy generated from the reaction is replaced by a calculated and controlled steam flow rate through a coil immersed in the reactor. A control valve is used to regulate the flow rate of fresh water into a heat exchanger. The heat exchanger then cools the process fluid and recycled it back to the reactor, hence controls the temperature of the reactor. The online fuzzy logic control results are made possible due to our developed customized graphical user and process interface. The work also highlights the software development involved. The software is designed so that it is capable of implementing several advanced nonlinear control strategies such as fuzzy logic